2003
DOI: 10.2214/ajr.181.6.1811669
|View full text |Cite
|
Sign up to set email alerts
|

Midline Prostatic Cysts in Healthy Men: Incidence and Transabdominal Sonographic Findings

Abstract: Midline prostatic cysts represent a common variant in asymptomatic men. In a patient with urologic symptoms, detection of a midline prostatic cyst requires a focused examination to determine whether the cyst represents a normal variant or is the cause of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 6 publications
0
16
0
4
Order By: Relevance
“…In this study, midline prostatic cysts were defined as hypoechoic to anechoic cystic lesions located in the midline of the prostate detected by transrectal ultrasound [1]. Computed tomography revealed a watery density zone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, midline prostatic cysts were defined as hypoechoic to anechoic cystic lesions located in the midline of the prostate detected by transrectal ultrasound [1]. Computed tomography revealed a watery density zone.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the widespread availability of transrectal ultrasound has led to an increase in diagnosis of prostatic cysts. It has been reported that midline prostatic cysts were observed in 7.6% of healthy men and 5% of symptomatic outpatients [1,2]. The majority of patients are symptom-free.…”
Section: Introductionmentioning
confidence: 98%
“…La présence d'une lésion obstructive de la partie distale du canal éjaculateur telle qu'un calcul, une infection chronique, une prostatite avec des sécrétions épaisses, des manipulations transurétrales ou un corps étranger permet de distinguer le kyste acquis du kyste congénital [11]. Par ailleurs, ces kystes sont remplis de spermatozoïdes et peuvent entraîner une infertilité d'origine obstructive [8].…”
Section: Kystes Des Canaux éJaculateursunclassified
“…En effet, les kystes d'origine müllérienne contiennent un liquide jaunâtre, caractérisé par l'absence de spermatozoïdes. Par contre, le kyste des canaux éjaculateurs renferme des spermatozoïdes, du fructose et parfois des calculs [11,16].…”
Section: Examens Paracliniquesunclassified
“…Prostatic cysts are observed in 0.5% to 7.9% of patients and are classified into six distinct types [1]. Most of them are origined from the posterior area of the prostate as an embriyologic remnant [2]. The semptomatic cysts may be confused with BPH or neuropatic bladder when they presented with lower urinary tract symptoms [3].…”
Section: Introductionmentioning
confidence: 99%